2015
DOI: 10.1158/1541-7786.mcr-15-0130
|View full text |Cite
|
Sign up to set email alerts
|

Patient Mutation Directed shRNA Screen Uncovers Novel Bladder Tumor Growth Suppressors

Abstract: Next generation sequencing (NGS) of human bladder cancer has revealed many gene alterations compared with normal tissue, with most being predicted to be “loss of function”. However, given the high number of alterations, evaluating the functional impact of each is impractical. Here we develop and use a high-throughput, in vivo strategy to determine which alterations are loss of function in tumor growth suppressors. Genes reported as altered by NGS in bladder cancer patients were bioinformatically processed by M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…This finding might partly explain why CAPAM KO strains are sensitive to oxidative stress. An RNA interference-based genetic screen identified CAPAM/PCIF1 as a putative tumor suppressor in a bladder cancer model (45), indicating that it might be involved in cell proliferation under certain conditions. Further studies seem necessary to unveil the physiological role of this gene.…”
Section: Discussionmentioning
confidence: 99%
“…This finding might partly explain why CAPAM KO strains are sensitive to oxidative stress. An RNA interference-based genetic screen identified CAPAM/PCIF1 as a putative tumor suppressor in a bladder cancer model (45), indicating that it might be involved in cell proliferation under certain conditions. Further studies seem necessary to unveil the physiological role of this gene.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, multiple studies indicated that TGF-β1 and its receptors stimulate the progression of bladder cancer cells. Loss of the IQGAP1 tumor suppressor leads to increased expression of TGFBR2 and activated the TGF-β1 signaling pathway, thereby stimulating growth of human bladder cancer cells [193]. TGF-β1-stimulated migration and invasion of bladder cancer cells arise mediated by Src and FAK kinase [194] as well as transgelin (TAGLN), an actin-binding protein that stimulates colony formation, migration, and invasion, as well as epithelial-mesenchymal transition [195].…”
Section: Bladder Cancermentioning
confidence: 99%
“…A previous study demonstrated that CTD affects gene expression in the human lung cancer NCI-H460 cell line ( 32 ). Additionally, a recent study identified, using next generation sequencing, that human bladder cancer has numerous gene alterations compared with normal tissue, with most predicted to be loss-of-function mutations; however, evaluating the functional impact of each genetic alteration is impractical ( 39 ). The present study, to the best of our knowledge, is the first to demonstrate the effects of CTD on gene expression in human bladder TSGH-8301 cancer cells.…”
Section: Discussionmentioning
confidence: 99%